AN ANALYSIS OF BANKRUPTCY PREDICTION IN MANUFACTURING FIRM BY USING BANKRUPTCY MODELS (CASE STUDY IN CHEMICAL SUB SECTOR LISTED IN INDONESIA STOCK EXCHANGE 2013-2017) - Siwi, Claudia Chyntia; Massie, James D.D; Tumewu, Ferdinand . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Indonesia has a big problem in the economic factor that caused by sharp declining value of the rupiah, the exchange rate rupiah toward US dollar fluctuations The declining value of rupiah right now can cause the bad impact for the manufacturing sector, especially in chemical sub sector, because the raw materials that used in that sector are import and they must use dollar for the payment. The aim of this research is to find out the bankruptcy prediction in manufacturing firm by using bankruptcy models. This research is an empirical study in the manufacturing firm, and using Altman Z-score and Zmijewski X-score to predict the bankruptcy. Based on the analysis with using the Altman Z-Score test show the results of companies manufacturing chemical sub-sectors those listed on the IDX do not all have bankrupt predictions. But have predictions bankrupt, gray area, and not bankrupt. In the last five years since 2013 until 2017 PT. Unggul Indah Cahaya and PT. Ekadharma International are in the not bankrupt category or health category. The investor should do the calculation z-score and x-score as a basis for consideration to make a decision whether to be used as an investment land.Â Keywords: bankruptcy prediction, bankruptcy model, altman z-score, zmijewski x-score.